PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN KEGIATAAN KESENMIAN REBANA ROUDATUL JANNAH RT 04 RW 05 KELURAHAN SEKIP KECAMATAN LIMA PULUH KOTA PEKANBARU - Astuti, Devi Sri; Bahar, Aswandi; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The purpose of this study is to determine the perception of society at RT 04 RW 05 Kelurahan Sekip Kecamatan Lima Puluh Kota Pekanbaru toward Rebana Roudatul Jannah activity. The activities consist of human resources, organizing and administrating. This is a descriptive study with a quantitative approach. The population in this study is society at RT 04 RW 05 (65 people) . The sample in this study are 39 people. Sampling in this study using Taro Yamane formula. The instrument in the study is a questionnaire containing 33 items of statements. The answer consists of four alternatives that are 1). strongly agree category (score 4), 2). agree scored 3 (three), 3). a score of 2 (two) is given to less agree and 4). disagree is scored 1 (one). The results revealed that the percception of society at RT 04 RW 05 Kelurahan Sekip Kecamatan Lima puluh Kota pekanbaru toward the rebana Roudatul Jannah interm of human resorces is 98,96% of the respondents strongly agree and agree, 2. Organizing is 94,53% 3. Administrasing is 95,89% of the respondent. It means that the implementation of the rebana Roudatul Jannah at RT 04 RW 05 Kelurahan Sekip Kecamatan Lima Puluh Kota Pekanbaru is executed properly.Key words : perception, society, activity, Rebana